Comparison of classical kinematics, entropy and fractal proprieties as measures of complexity of the motor control in swimming - Barbosa, Tiago (2016)
The aim of this study was to compare the non-linear properties of the four competitive swim strokes. Sixty-eight swimmers performed a se tof maximal 4×25m using the four competitive swimstrokes. The hip’s speed-data as a function of time was collected with a speedo-meter. The speed fluctuation (dv), approximate entropy(ApEn) and the fractal dimension by Higuchi’s method (D) were computed. Swimming data exhibited non-linear properties tha twere different among the four strokes (14.048 ≤dv≤ 39.722; 0.682 ≤ApEn≤ 1.025; 1.823 ≤D≤ 1.919). The ApEn showed the lowest value for front-crawl, followed by breaststroke, butterfly, and backstroke (P<0.001). Fractal dimension and dv had the lowest values for front-crawl and backstroke, followed by butterfly and breaststroke (P<0.001). It can be concluded that swimming data exhibitsnon-linear properties, which are different amongthe four competitive swimming strokes.